Popovych M. M. Semantic features of linguo-cognitive concept–mental space - Popovych M. M. (Philological Treatises, 2020)
The author of the paper argues with cognitive scientists about the novelty of cognitive-discourse paradigm of modern linguistic researches and analyses some contradictory aspects of interpretation of the most fundamental concept of cognitive linguistics – mental space